Efektivitas penggunaan tongue scraper terhadap penurunan indeks tongue coating dan jumlah koloni bakteri anaerob lidah Effectivity of tongue scraper on reducing tongue coating and anaerobic bacteria colony count - Hamdini Hamid; Rabia’tul Aulia; Rasmidar Samad (Journal of Dentomaxillofacial Science, 2011)
Many microorganisms have been found colonizing the dorsum of tongue. To prevent infection and development ofother pathologies in oral cavity, tongue cleaning has been advocated to reduce the amount of coating andmicroorganism loading in the mouth. The aim of this study is to find out the impact of tongue cleaning using tonguescraper against tongue coating index and anaerobic bacterial colony count on tongue dorsum. This study wascarried out on 24 male and 16 female participants aged 11 to 17. Tongue coating index was used to assess tonguecoating and tongue samples were taken to count the bacterial colony. The result showed that there is a significantdifference tongue coating index (Wilcoxon Signed Rank test, p=0.000) and amount of anaerobic bacteria colony (tpairedtest, p=0.007)before and after using tongue scraper. In conclusion, tongue scraper can reduce tonguecoating index and there was significant difference in anaerobic bacteria colony count before and after using tonguescraper.